The role of tea in managing cardiovascular risk factors: potential benefits, mechanisms, and interventional strategies - Xu, Ziming; Tao, Zhu; Guo, Yan (Frontiers in Nutrition, 2025)
Traditional major cardiovascular disease (CVD) risk factors include dyslipidemia, hypertension, smoking, diabetes, and obesity. Tea is rich in various bioactive substances such as tea polyphenols, theaflavins, and tea polysaccharides. Due to the regulatory effects on multiple pathways and its anti-inflammatory and antioxidant properties, these active substances have shown significant efficacy in regulating dyslipidemia, hypertension, diabetes, obesity, and cardiac autonomic function. Additionally, tea possesses anti-inflammatory and antithrombotic properties, making it a promising dietary supplement for nutritional interventions in the primary and secondary prevention of CVDs. However, the complex composition of tea, although shown to have certain effects in vivo, does not fully elucidate the specific mechanisms of action. Moreover, the varying application methods across different studies lead to differences in intervention effects and dose–response relationships, sometimes resulting in contradictory findings. This article reviews the potential benefits, mechanisms of action, and application methods of tea for cardiovascular risk factors, elucidating its potential as a nutritional intervention.